CRITICAL DISCOURSE ANALYSIS OF THE CONSTRUCTION OF POVERTY REDUCTION POLICIES IN THE 2025–2029 RPJMA ACEH - Alfian; Yuli Santri Isma; Fitria Akmal; Sarrah Kurnia Fadhilah; Asmaul Husna (RADJA PUBLIKA, 2026)
Poverty remains a major development issue in Aceh despite the province's substantial fiscal space through the Special Autonomy Fund. This study aims to analyze how poverty, development actors, and collaborative governance are constructed in the Aceh Medium-Term Development Plan (RPJMA) 2025–2029. This study uses a qualitative approach with a constructivist paradigm and Norman Fairclough's Critical Discourse Analysis method . The research data source is the Aceh RPJMA 2025–2029 document, which is analyzed using Fairclough's three dimensions: text analysis, discursive practices, and social practices. The results show that poverty in the Aceh RPJMA is constructed as an issue structurally subordinate to the agenda of Aceh's identity and uniqueness. The discourse of collaborative governance is not strongly and consistently present in the strategic formulation of poverty alleviation policies, in contrast to issues such as health, education, and research-innovation, which explicitly present collaborative narratives. Furthermore, fragmentation of accountability is found through the use of separate poverty indicators between the macroeconomic and social welfare domains without a clear integration mechanism. These findings demonstrate a gap between development rhetoric that ambitiously targets poverty reduction and the limited collaborative institutional design. This research contributes to the development of public policy studies by demonstrating that development planning documents constitute a discursive arena that represents power relations, development priorities, and the construction of policy governance.